Dynamic model of a badminton stroke - Kwan, M.; Andersen, M. S.; de Zee, M.; Rasmussen, J. (The Engineering of sport 7, Volume 2, 2008)
The purpose of this paper is to contribute to the understanding of dynamic racket behaviour in badminton. The paper describes the development of a dynamic model of a badminton stroke based on experimental data. Motion capture and strain gauge experiments are performed to clarify the movement and accelerations of a badminton smash stroke. Subsequent data processing reveals that due to the speed and acceleration of the movement, neither of the two methods provides the complete picture of the racket's dynamic behaviour, but computational processing of the combination of experimental data together with physical modelling of the racket mechanics allows for an understanding of the basic mechanisms underlying racket movement and deformation. The paper concludes that the elastic deflection of the racket creates a narrow window of opportunity during which the impact is enhanced by the racket's elastic behaviour, and this window must be closely synchronized with the timing of the stroke.